Roman to early medieval cereal farming in the Rhineland: weeds, tillage, and the spread of the mouldboard plough - Hamerow, HF; Zerl, T; Kropp, C; Bogaard, A (Routledge, 2024)
A new model for gauging levels of soil disturbance (i.e. tillage) by analysing arable weed assemblages from archaeological contexts is applied to an extensive Roman-to-early medieval archaeobotanical sequence from the region west of Cologne. It tests the hypothesis that increasing use of the mouldboard plough, especially in a three-field system, would result in increased levels of soil disturbance which would be reflected in the kinds of weeds that grew in arable fields. The results point to clear differences in tillage regimes during the Roman period, providing support for the view that military sites were not provisioned by the same networks that supplied the civilian market. They also reveal generally low disturbance levels for the fifth and sixth centuries, indicating a continuing predominance of ard cultivation in the post-Roman period. The majority of seventh- to eighth-century samples had, however, been grown in ‘high disturbance’ conditions, a pattern that continued through the eighth and ninth centuries. Although use of the mouldboard plough within a fully developed three-field system may not have become widespread until the tenth or eleventh century, our evidence suggests that a plough capable of turning over the soil was in use in the Rhineland at a much earlier date.